2012
DOI: 10.1177/1056492612448463
|View full text |Cite
|
Sign up to set email alerts
|

Recontextualizing Anthropomorphic Metaphors in Organization Studies

Abstract: In this article, the authors discuss critically the use of "anthropomorphic" metaphors in organization studies (e.g., organizational knowledge, learning, and memory). They argue that, although these metaphors are potentially powerful, because of frequent usage they are at risk of becoming taken for granted and contextually disconnected from their source domain, the human mind. To unleash the heuristic potential of such metaphors, it is necessary to take into account the inherent dynamics and bidirectionality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 89 publications
(205 reference statements)
0
26
0
Order By: Relevance
“…For instance, evaluators have been found to draw on the concept of ''space'' to comprehend the more abstract concept of ''time,'' such as in ''we are looking forward to a brighter tomorrow'' or ''falling behind schedule'' (Boroditsky 2000, p. 4). Likewise, organization theory scholars have suggested that thinking and speaking of organization and organizing is inherently metaphorical in nature (Cornelissen 2004(Cornelissen , 2005Schoeneborn et al 2013), as exemplified by the use of anthropomorphic metaphors to describe organizational characteristics and functions, such as in the ''organizational identity'' and the ''learning organization'' metaphors (Cornelissen 2005).…”
Section: The Role Of Conceptual Metaphor In Judging Transnational Govmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, evaluators have been found to draw on the concept of ''space'' to comprehend the more abstract concept of ''time,'' such as in ''we are looking forward to a brighter tomorrow'' or ''falling behind schedule'' (Boroditsky 2000, p. 4). Likewise, organization theory scholars have suggested that thinking and speaking of organization and organizing is inherently metaphorical in nature (Cornelissen 2004(Cornelissen , 2005Schoeneborn et al 2013), as exemplified by the use of anthropomorphic metaphors to describe organizational characteristics and functions, such as in the ''organizational identity'' and the ''learning organization'' metaphors (Cornelissen 2005).…”
Section: The Role Of Conceptual Metaphor In Judging Transnational Govmentioning
confidence: 99%
“…Unlike the mechanisms of state governance, TGSs, as well as their organizational structures, procedures, and outcomes, are as yet poorly understood (Djelic and Quack 2008;Stone 2008). Drawing on research in cognitive linguistics (Lakoff 1996(Lakoff , 2008Lakoff & Johnson 1980) and organization theory (Cornelissen 2004;Schoeneborn et al 2013), we argue that in order to make sense of the complexities of TGSs, evaluators often automatically apply concepts from domains they are more familiar with. That is, the conceptual structure underlying evaluators' reasoning about TGSs such as the UNGC is to a large extent metaphorical.…”
Section: Introductionmentioning
confidence: 99%
“…The first (potential) shortfall arises from a theorizing outcome that is separated from the original assumptions, propositions and related observables (Cronbach & Meehl, 1955;Schoeneborn, Blaschke & Kaufmann, 2013) and, as a result, there is a lost opportunity to engage in multi-level theorizing (Lane, Koka & Pathak, 2006;Thompson, 2011). The second (potential) shortfall arises from borrowing concepts, relationships, and theories, where there is insufficient regard to their relevance as organizational theories (Whetten, Felin, & King, 2009).…”
Section: Downloaded By [University Of Sussex Library] At 03:32 05 Febmentioning
confidence: 96%
“…The latter path is more challenging and fraught with difficulties. Alvesson et al (2017) suggest that academics adopt polymorphic approaches travelling between disciplines and seeking out academic adventures, to allow ideas to cross-fertilize, and bring novelty to both domains (Schoeneborn et al, 2013). This requires a shift in how individual academics view their role and the careers they follow, and at the same time, institutions need to nurture and develop this process of emergence (see below).…”
Section: The Call For Academics To Search For Noveltymentioning
confidence: 99%